Impact of Soil Disinfestation on Fungal and Bacterial Communities in Soil With Cucumber Cultivation - Wang, Yan; Jin, Yujie; Han, Ping; Hao, Jianjun; Pan, Hongyu; Liu, Jinliang (Frontiers in Microbiology, 2021)
Soil treatment with disinfectants has been used in controlling plant pathogens in soil. Beside of beneficial effects, their potential impact on soil health by affecting beneficial microbes is yet to be determined. The objectives of this study were to examine the effects of three disinfectants, including the dazomet fumigant, fenaminosulf fungicide and kasugamycin antibiotics, on chemical properties, enzymatic activities, and microbial communities in soil for cucumber cultivation. Results showed that 14 days after soil treatment with these chemicals, residual content of dazomet and kasugamycin quickly declined in soil and were undetectable, but fenaminosulf was 0.48 ± 0.01 mg/kg. Total nitrogen and total carbon increased in soil by dazomet treatment. Urease and sucrase activities were significantly restrained after disinfectant application. Disinfectants did not significantly change the taxon of predominant bacteria and fungi but altered relative abundance and diversity of soil microbiome. Cucumber cultivation enhanced soil microbial diversity and enzymatic activities. Both disinfectants and cucumber cultivation changed interspecific relationship of soil microbial communities. The difference of soil microbial diversity among four treatments became smaller after planting cucumber. Thus, soil disinfectants affected soil microbiome but did not affect the taxon of predominant microbes in soil and planting cucumber would gradually restore the soil health.